2021
DOI: 10.1093/nar/gkab619
|View full text |Cite
|
Sign up to set email alerts
|

Two isoforms of the essential C. elegans Argonaute CSR-1 differentially regulate sperm and oocyte fertility

Abstract: The Caenorhabditis elegans genome encodes nineteen functional Argonaute proteins that use 22G-RNAs, 26G-RNAs, miRNAs or piRNAs to regulate target transcripts. Only one Argonaute is essential under normal laboratory conditions: CSR-1. While CSR-1 has been studied widely, nearly all studies have overlooked the fact that the csr-1 locus encodes two isoforms. These isoforms differ by an additional 163 amino acids present in the N-terminus of CSR-1a. Using CRISPR-Cas9 genome editing to introduce GFP::3xFLAG into th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 94 publications
7
53
0
Order By: Relevance
“…We combined our worm population sorting strategy with CSR-1 or HRDE-1 IPs, followed by small RNA sequencing. Given the expression of two isoforms of CSR-1 in the L4 stage ( Charlesworth et al., 2021 ; Nguyen and Phillips, 2021 ), we verified the enrichment of both CSR-1 isoforms 22G-RNA targets in our sorted CSR-1 IPs ( Figure S7 A). The analysis of 22G-RNAs from sorted early L4 to young adult worms showed that oogenic 22G-RNAs were globally loaded into CSR-1 but not in HRDE-1 ( Figure S7 B).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…We combined our worm population sorting strategy with CSR-1 or HRDE-1 IPs, followed by small RNA sequencing. Given the expression of two isoforms of CSR-1 in the L4 stage ( Charlesworth et al., 2021 ; Nguyen and Phillips, 2021 ), we verified the enrichment of both CSR-1 isoforms 22G-RNA targets in our sorted CSR-1 IPs ( Figure S7 A). The analysis of 22G-RNAs from sorted early L4 to young adult worms showed that oogenic 22G-RNAs were globally loaded into CSR-1 but not in HRDE-1 ( Figure S7 B).…”
Section: Resultsmentioning
confidence: 68%
“…We followed the subcellular localization of piRNA pathway components during spermatogenesis to discern the spatiotemporal specificity of nuclear piRNA-dependent signaling. In parallel, we studied the localization of CSR-1, a germline AGO protein highly enriched in P granules ( Claycomb et al., 2009 ) and also present in Z granules ( Charlesworth et al., 2021 ), another type of biomolecular condensate part of the C. elegans nuage ( Wan et al., 2018 ). We confirmed the co-localization of PIWI and CSR-1 with GLH-1, the C. elegans homolog of the DEAD-box RNA helicase Vasa, a core P granule component ( Figure S2 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSR-1 suppresses HCP-3 via its RNAi pathway and with its slicing activity. The regulation likely happens in the hermaphrodite germline where the CSR-1 isoform b is enriched (Charlesworth et al, 2021). Specific depletion of the other soma cells-enriched isoform a does not cause embryonic lethality (Claycomb et al, 2009, Gerson-Gurwitz et al, 2016, chromosome missegregation, as well as a dramatic GFP::HCP-3 elevation as the depletion of both isoforms does.…”
Section: Discussionmentioning
confidence: 99%
“…To deplete only CSR-1A, we use dsRNA targeting the first exon of isoform A. As depletion of CSR-1A alone is not embryonic lethal (Gerson-Gurwitz et al, 2016, Charlesworth et al, 2021, we validated the csr-1a knockdown by RT-PCR, whose mRNA level is 12.23% of that in the untreated embryos (Figure S3B). Depletion of CSR-1A results in 1.3-fold increase in chromatin GFP::HCP-3 level in 1-cell stage embryos, compared to the untreated control (Figure 3E).…”
Section: The Increase In Hcp-3 Chromatin Localization Was Not Depende...mentioning
confidence: 99%